Assessing Infant Feeding Attitudes of Expectant Women in a Provincial Population in Canada: Validation of the Iowa Infant Feeding Attitude Scale. (August 2016) - Twells, Laurie K.; Midodzi, William K.; Ludlow, Valerie; Murphy-Goodridge, Janet; Burrage, Lorraine; Gill, Nicole; Halfyard, Beth; Schiff, Rebecca; Newhook, Leigh Anne
Background: Maternal attitudes to infant feeding are predictive of intent and initiation of breastfeeding. Objectives: The Iowa Infant Feeding Attitude Scale (IIFAS) has not been validated in the Canadian population. This study was conducted in Newfoundland and Labrador, a Canadian province with low breastfeeding rates. Objectives were to assess the reliability and validity of the IIFAS in expectant mothers; to compare attitudes to infant feeding in urban and rural areas; and to examine whether attitudes are associated with intent to breastfeed. Methods: The IIFAS assessment tool was administered to 793 pregnant women. Differences in the total IIFAS scores were compared between urban and rural areas. Reliability and validity analysis was conducted on the IIFAS. The receiver operating characteristic (ROC) of the IIFAS was assessed against mother's intent to breastfeed. Results: The mean ± SD of the total IIFAS score of the overall sample was 64.0 ± 10.4. There were no significant differences in attitudes between urban (63.9 ± 10.5) and rural (64.4 ± 9.9) populations. There were significant differences in total IIFAS scores between women who intend to breastfeed (67.3 ± 8.3) and those who do not (51.6 ± 7.7), regardless of population region. The high value of the area under the curve (AUC) of the ROC (AUC = 0.92) demonstrates excellent ability of the IIFAS to predict intent to breastfeed. The internal consistency of the IIFAS was strong, with a Cronbach's alpha greater than .80 in the overall sample. Conclusion: The IIFAS examined in this provincial population provides a valid and reliable assessment of maternal attitudes toward infant feeding. This tool could be used to identify mothers less likely to breastfeed and to inform health promotion programs.